An end to graded lessons: the opportunity to construct a developmental observation model as a tool to improve teaching and learning in a secondary high school. - Dicksee, Ian (2016)
The purpose of this study is to scrutinise teachers’ perceptions of the role of lesson observations in their professional lives; it explores what the key features of a lesson observation process are that would best support teachers in developing their classroom practice, rather than judging it. The research examines teachers’ attitudes towards the challenges of observing ‘typicality’, who is best placed to observe other colleagues, managing the transition from observation to discussion, and the nature of that professional dialogue. A questionnaire with both closed-ended and open-ended questions has provided a mixed method, concurrent approach to the data collection, targeting all teaching staff in one secondary school. The findings demonstrate strong support for lesson observations functioning as a developmental tool for improving teaching and learning. There is a tension between the impromptu observation of ‘typicality’ and consequential teacher anxiety, but a convincing mandate is provided for the shared ownership of a follow-up dialogue that reflects on what was observed, why it happened, and how it can be improved.